Dilema Siaran Keagamaan di Radio Dalam Menghadapi Digitalisasi Media (Studi Kasus K Radio Jember) - Vaylasufah Selma; Muhibbin (Maddah: Journal of Advanced Da'wah Management Research, 2022)
The very rapid development of information and communication technology has made the world community move from the traditional era to the revolutionary era where all information is easy to obtain, as well as religious broadcasts that are easily obtained through social media. However, radio, which is a conventional media, still maintains religious broadcasts, this is what happened to K Radio which until now has been able to maintain religious broadcast programs. The focus of the problems that will be discussed in this thesis are: 1) What are the factors that support religious broadcast programs on radio being able to survive in the midst of rampant broadcasts on social media? 2) How do the managers of religious broadcasting programs on radio try to stay afloat in the midst of rampant broadcasts on social media? 3) What is the impact of the sustainability of religious broadcast programs on radio in the face of rampant broadcasts on social media?. The objectives of this study are: 1) To find out the supporting factors for religious broadcasting programs that are able to survive in the midst of the proliferation of broadcasts on social media. 2) To find out the efforts made by the managers of religious broadcast programs to stay afloat in the midst of rampant broadcasts on social media. 3) To find out the impact of the sustainability of religious broadcast programs in the face of rampant broadcasts on social media. This study used qualitative research methods.. Data collection techniques were obtained from observations, in-depth interviews, and documentation. The results obtained from this study are: 1) the factors that support religious broadcasting programs are due to the quality of human resources and program management. 2) the efforts made by the manager are program branding and collaboration. 3) the impact of sustainability that occurs is in terms of economy, human resources, and institutions.